Changing urban green spaces in Shanghai: trends, drivers and policy implications. (September 2019) - Wu, Zhen; Chen, Ruishan; Meadows, Michael E.; Sengupta, Dhritiraj; Xu, Di
Highlights: Understanding of urban green spaces dynamics are required to improve urban sustainability. Green spaces in the city center of Shanghai shifted from a net loss to net gain from 1980 to 2015. The shape and distribution of urban green spaces have become more regular and less fragmented. Population growth and greening policies are major drivers of green spaces change. Abstract: Urban green spaces play a range of significant roles and have a positive influence on the quality of life in cities. Shanghai, a major economic and financial center in China, has set its goal to become a more ecologically integrated and livable city. The urban authorities envisage Shanghai as "a city in the forest, a forest in the city". To achieve this greener future, the government has developed a series of policies to improve urban greening coverage. Based on land use and land cover data from 1980 to 2015, this paper analyzes temporal and spatial changes in urban green spaces in Shanghai, and explores the driving forces underlying the observed changes. Although the total urban green spaces in Shanghai declined from 1980 to 2015, different districts have different trends. Urban green spaces in the suburbs and the islands have declined, although, the city center increased its green spaces following several decades of decrease. Several factors have contributed to these changes, including population increase, conflicting government policies, real estate development, and rising demand for recreation space. Knowledge of the dynamics of urban green spaces in the city can assist in fostering an appropriate balance between urban development and environmental protection. To prevent environmental degradation and to plan a restoration pathway, cities should attempt to keep green spaces in mind during the development process and integrate the green spaces into urban planning. Understanding the dynamics of green spaces in Shanghai may offer insights for other cities in developing their own green spaces.